Lumberjanes. Volume sixteen, Mind over mettle - Watters, Shannon; Leyh, Kat (Boom! Box, 2020)
Mal wants to learn how to be braver, but things go sideways when Ripley's plan to help her accidentally sends her to an alternate dimension where dinosaurs still roam, the Land of Lost Things. Mal becomes trapped and has to find a way back to camp. On the other side of the portal, Molly, April, Jo, and Ripley try to find Mal and bring her home.